1968
DOI: 10.1111/j.1365-2621.1968.tb03669.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Bacteria for Quaternary Ammonium Compounds

Abstract: Escherickia coli and Pseudomonas fluorescens followed similar patterns of adaptation to tolerate quaternary ammonium compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…aeruginosa to quaternary compounds sevenfold from 100 to 700 parts per million after nine transfers in a liquid medium, and ultimately to 2000 parts per million. Increased tolerance of Gram-negative bacteria to these antiseptics has also been reported by Soprey and Maxcy (1968). Organisms resistant to chlorhexidine have been reported by Gillespie et al (1967), Stickler (1974), andMaurer (1974).…”
Section: Discussionmentioning
confidence: 86%
“…aeruginosa to quaternary compounds sevenfold from 100 to 700 parts per million after nine transfers in a liquid medium, and ultimately to 2000 parts per million. Increased tolerance of Gram-negative bacteria to these antiseptics has also been reported by Soprey and Maxcy (1968). Organisms resistant to chlorhexidine have been reported by Gillespie et al (1967), Stickler (1974), andMaurer (1974).…”
Section: Discussionmentioning
confidence: 86%
“…Resistance to quaternary ammonium compounds has been reported in a number of Gramnegative species (Chaplin, 1952;MacGregor and Elliker, 1958;Soprey and Maxcy, 1968) and Mac-Gregor and Elliker suggested that in the case of Pseudomonas aeruginosa resistance was due to a modification of the cell wall, which obstructed the penetration of the bactericide. Bentley, Davies, Field, and Roberts (1968) reported that a strain of Pseudomonas species able to grow in media contamiing up to 200 ug of chlorhexidine/ml had a lower capacity than normal strains for absorbing the bactericide from the growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…Both Foster et al (1958) and Newton (1958) have reported that quaternary ammonium compounds are more effective against gram positive bacteria than gram negative ones. In addition, Soprey and Maxcy (1968) have demonstrated that Pseudomonas fluorescens and Escherichia coli can adapt to tolerate quaternary ammonium compounds.…”
Section: Resultsmentioning
confidence: 98%